Proteomics of Rice—Magnaporthe oryzae Interaction: What Have We Learned So Far? - Meng, Qingfeng; Gupta, Ravi; Min, Cheol Woo; Kwon, Soon Wook; Wang, Yiming; Je, Byoung Il; Kim, Yu-Jin; Jeon, Jong-Seong; Agrawal, Ganesh Kumar; Rakwal, Randeep; Kim, Sun Tae (Frontiers in Plant Science, 2019)
Rice blast disease, caused by Magnaporthe oryzae, is one of the major constraints to rice production, which feeds half of the world’s population. Proteomic technologies have been used as effective tools in plant−pathogen interactions to study the biological pathways involved in pathogen infection, plant response, and disease progression. Advancements in mass spectrometry (MS) and apoplastic and plasma membrane protein isolation methods facilitated the identification and quantification of subcellular proteomes during plant-pathogen interaction. Proteomic studies conducted during rice−M. oryzae interaction have led to the identification of several proteins eminently involved in pathogen perception, signal transduction, and the adjustment of metabolism to prevent plant disease. Some of these proteins include receptor-like kinases (RLKs), mitogen-activated protein kinases (MAPKs), and proteins related to reactive oxygen species (ROS) signaling and scavenging, hormone signaling, photosynthesis, secondary metabolism, protein degradation, and other defense responses. Moreover, post−translational modifications (PTMs), such as phosphoproteomics and ubiquitin proteomics, during rice−M. oryzae interaction are also summarized in this review. In essence, proteomic studies carried out to date delineated the molecular mechanisms underlying rice-M. oryzae interactions and provided candidate proteins for the breeding of rice blast resistant cultivars.